29.3k views
2 votes
Which is a solution of x2 – x – StartFraction 3 Over 4 EndFraction = 0?

1 Answer

4 votes

Answer:

x = -
(1)/(2), x =
(3)/(2)

Explanation:

Given

x² - x -
(3)/(4) = 0 ( add
(3)/(4) to both sides )

x² - x =
(3)/(4)

Solve using the method of completing the square

add ( half the coefficient of the x- term )² to both sides

x² + 2( -
(1)/(2) )x +
(1)/(4) =
(3)/(4) +
(1)/(4)

(x -
(1)/(2) )² = 1 ( take the square root of both sides )

x -
(1)/(2) = ± 1 ( add
(1)/(2) to both sides )

x =
(1)/(2) ± 1

Thus

x =
(1)/(2) - 1 = -
(1)/(2)

x =
(1)/(2) + 1 =
(3)/(2)

User Oggy
by
6.0k points